SELF- EFFICACY DAN SELF- REGULATION SEBAGAI UNSUR PENTING DALAM PENDIDIKAN KARAKTER (Aplikasi Pembelajaran Mata Kuliah Akhlak Tasawuf) - Vivik Shofiah Raudatussalamah (Kutubkhanah, 2015)
This study investigates the character education through the study of Sufism Morals to increase self-efficacy and self-regulation of students UIN Sultan Syarif Kasim Riau. The measurement of self-efficacy and self-regulation were using the Self-efficacy scale consist of 10 item and self-regulation scale consist of 25 item. The total number of resondent of this research were 800 student. The data was analyzed using multivariate analysis technique. The result show that the learning Morals Sufism can increase selfefficacy and self-regulation of student of UIN Suska Riau